Неосвіченість суспільства як фактор поширення маніпулювання суспільними настроями - Абрамов, Федір Володимирович (Видавничий дім "Інжек", 2019)
Метою статті є визначення впливу неосвіченості суспільства на поширення практики маніпулювання суспільними настроями. Доведено, що неосвіченість населення є одним із факторів, які можуть сприяти зростанню занепокоєння суспільства, що створює сприятливі умови для маніпулювання суспільними настроями. Показано, що гравець-маніпулятор може експлуатувати неосвіченість населення через реалізацію одної з двох стратегій: стратегії залякування та стратегії виправдання. У випадку стратегії залякування гравець-маніпулятор, зловживаючи неосвіченістю населення, поширює неправдиву інформацію з метою дискредитації та усунення конкурента. У випадку стратегії виправдання гравець-маніпулятор експлуатує неосвіченість суспільства для введення його в оману стосовно необхідності окремих заходів чи інституційних реформ. Доведено, що необхідною умовою попередження маніпулювання суспільними настроями, що базується на експлуатації неосвіченості суспільства, є покращення якості загальної складової освіти та формування широкого світогляду членів суспільства.

The article is aimed at defining the impact of society’s lack of education on the spread of the practice of manipulating with public sentiments. It is been proved that the lack of education of the population is one of the factors that can contribute to the increase of social anxiety, which creates favorable conditions for manipulating with public sentiments. It is shown that an actor-manipulator can exploit the lack of education of the population by implementing one of two strategies: strategy of intimidation and strategy of justification. In the case of a strategy of intimidation, the actor-manipulator, taking advantage of the lack of education of the population, disseminates false information in order to discredit and eliminate the competitor. In the case of a strategy of justification, the actor-manipulator exploits the lack of education of the population in order to mislead the latter about the need for separate measures or institutional reforms. It is proved that the necessary condition to prevent the manipulation of public sentiments, which are based on the exploitation of the society’s lack of education, is to improve the quality of the general component of education and to gain the formation of a broader range of worldviews of the society’s members.
The society's lack of education as a factor in the spread of manipulation with public sentiment
Keywords: освіта; інституційні рамки; навчальний процес; економіка; корупція; ринок праці; education; institutional framework; manipulation; public sentiments